Free-living marine polychaetes (Annelida) inhabiting hard-bottom substrates in Trinidad and Tobago, West Indies - F. Gobin, Judith (2010)
As part of a larger comparative study, marine polychaete hard-bottom assemblages were surveyed using artificial substrate units (ASUs) deployed at four sites off the islands of Trinidad and Tobago. The polychaete fauna was represented by 19 families comprising 89 species. The syllid Exogone dispar was the most abundant polychaete followed closely by the serpulid Pseudovermilia occidentalis. At the family level, the polychaete fauna inhabiting the ASUs is similar to the fauna from other temperate and tropical locations. Omnivorous species were dominant (70 %), followed by filter feeders (20%). This survey provides first records of the hard-bottom polychaete fauna of Trinidad and Tobago and adds new information about the geographic range of some polychaete species.